A numerical strategy for predicting the coupling-strength of acoustic fluid-structure interaction. (15th January 2023) - Fang, Chen; Zeng, Yaoxiang; Zhang, Yahui
Highlights: A coupling-strength factor is proposed for acoustic fluid–structure interaction. An efficient numerical strategy is built by a fast dynamic flexibility algorithm. Resonance analysis can verify the proposed coupling-strength analysis strategy. The factor can high-efficiently predict the coupling-strength. Abstract: The coupling-strength analysis can guide the proper modeling and efficient response analysis for acoustic fluid–structure problems. In this paper, a coupling-strength factor is proposed to quantify the dynamic interaction between acoustic fluid and structure, and its efficient computational strategy is established via a fast algorithm. This dimensionless factor expresses the average difference between the uncoupled and the coupled structural displacement (acoustic pressure) fields. The factor expression is related to the coupling matrix and the dynamic flexibility matrices of each physical field for the discrete system. Then a fast dynamic flexibility matrix algorithm of the non-positive definite system is deduced to ensure the feasibility of numerically calculating the factor, and the effects of the unconstrained structure and the acoustic rigid wall on the coupling-strength can be observed. Additionally, the strongly decoupling eigen-equations of each physical field are derived by the dynamic flexibility matrix expansion. Solving the resonance frequencies is adopted to verify the correctness of the proposed coupling-strength analysis strategy. In numerical examples, the coupling-strength factor is high-efficiently calculated with acceptable accuracy, the coupling-strength is investigated for the various acoustic fluid mediums and different boundary conditions, and the applicability and effectiveness of the factor are verified.